1997
DOI: 10.1103/physrevb.56.5286
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic dynamics of the glass transition investigated by time-resolved fluorescence measurements of doped chromophores

Abstract: The microscopic dynamics of several monomeric and polymeric glass-forming materials has been investigated by time-resolved fluorescence measurements of doped malachite green molecules in a wide temperature region. For monomers, 1-propanol, propylene glycol, and glycerol, and a polymer without side chains, polybutadiene, the temperature dependence of nonradiative decay time of doped malachite green molecules behaves in a similar way through the glass-transition region. Besides a kink around the calorimetric gla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
70
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(77 citation statements)
references
References 63 publications
6
70
1
Order By: Relevance
“…that also were found to work in other ESR studies by us [14][15][16][17], and also with other kinds of probe spectroscopy [11].…”
Section: Materials and Experimental Detailssupporting
confidence: 55%
See 2 more Smart Citations
“…that also were found to work in other ESR studies by us [14][15][16][17], and also with other kinds of probe spectroscopy [11].…”
Section: Materials and Experimental Detailssupporting
confidence: 55%
“…For all the investigated samples, the crossover between the two regimes takes place at a temperature C T located in the range 1.15-1.25T g (see table 5) that well agrees with the critical temperature range of the mode coupling theory [30], and with related recent experimental studies [7] in polymers. In this temperature interval, crossovers between different dynamic regimes in glass-formers are also a current finding of various spectroscopies [5,6,11,12]. The above result on PAAs intrigues and proposes the ESR as a major spectroscopy to investigate the crossover dynamics.…”
Section: Materials and Experimental Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…The temperature dependence of the luminescence of several guests or labels in polymers is a complex process and different approaches have been employed [10][11][12][13][14][15][16][17][18][19][20][21][22]. It was demonstrated that phosphorescence emission of several probes sorbed in different polymers were able to detect the…”
Section: Micromorphology and Relaxation Processes Of Low Density Polymentioning
confidence: 99%
“…Additional focuses were introduced in studies of the temperature dependence of the luminescence properties of fluorescent condensed aromatic hydrocarbons, because they allowed the determination of the polymer relaxation processes [10][11][12][13][14][15][16][17][18][19][20][21][22]. Luminescent polymers necessary for these studies may be produced by several methods: copolymerization of luminescent monomers, sorption of luminescent guests in a polymer host and chemical modification of pre-formed polymer attaching luminescent groups [11,12,[16][17][18][19][20][23][24][25].…”
Section: Micromorphology and Relaxation Processes Of Low Density Polymentioning
confidence: 99%